CSNK1A1 mutations and isolated del(5q) abnormality in myelodysplastic syndrome: a retrospective mutational analysis. Issue 5 (May 2015) - Smith, Alexander E; Kulasekararaj, Austin G; Jiang, Jie; Mian, Syed; Mohamedali, Azim; Gaken, Joop; Ireland, Robin; Czepulkowski, Barbara; Best, Steven; Mufti, Ghulam J
Summary: Background: A mechanism for clonal growth advantage in isolated del(5q) disease remains elusive. CSNK1A1 resides on the critically deleted region, and deletion of this gene has been shown in mouse knockout and transplantation studies to produce some characteristics of bone marrow failure, including a proliferative advantage. We aimed to establish the frequency, nature, and clinical association of CSNK1A1 mutations in patients with myelodysplastic syndrome and associated myeloid neoplasms. Methods: Between June 1, 2004, and May 31, 2014, in King's College (London, UK), we did whole-exome sequencing of five patients with isolated del(5q) followed by targeted screening for CSNK1A1 mutations and 20 myelodysplastic syndrome-associated mutations in 245 additional patients with myeloid neoplasms. All patients met present WHO diagnostic criteria for myelodysplastic syndrome and other related myeloid neoplasms. Findings: 39 (16%) of 250 patients with myeloid neoplasms had isolated del(5q), of whom seven (18%) had CSNK1A1 mutations. All these mutations were missense and presented in a highly conserved region that is implicated in ATP catalysis. Serial sampling and response to lenalidomide treatment showed that CSNK1A1 mutations were highly associated with the del(5q) clone. Only one patient with a CSNK1A1 mutation showed complete cytogenetic response to lenalidomide. Four (57%) of the seven patients carrying a CSNK1A1 mutation showed disease progression coupled with an increase in mutant allele burden (all four were on lenalidomide). We detected coexisting myelodysplastic syndrome-related gene mutations in patients with CSNK1A1 mutations, including TP53 . Interpretation: Similar to the effect of TP53 mutations on progression of del(5q) abnormality, mutant CSNK1A1 also gives rise to a poor prognosis in del(5q) abnormality, for which a coupled increase in P53 activation is suggested. CSNK1A1 mutations in del(5q) disease are important in the context of therapeutic manipulation and need incorporation into future prospective studies. Funding: Leukaemia and Lymphoma Research.